(untitled) (Interdisciplinary Studies Journal, 2026)
This study, conducted within the Master’s Program in Teaching (PPGEnsino) – Univates, analyzed the participants’ understanding of Sexuality Education, including Identities, Genders, Sexualities, and Diversity, as well as the need for pedagogical practices in this field. A questionnaire was applied through Google Forms, disseminated via social media, inviting teachers with experience in teaching high school in Mato Grosso from 2018 to 2024. The data revealed a more inclusive perspective on incorporating Sexuality Education into teaching, highlighting the importance of addressing this topic in the classroom. This approach can strengthen students’ critical thinking skills through dialogue and science, fostering the construction of new knowledge and contributing to the reduction of taboos and prejudices. Additionally, it provides an opportunity to inform, prevent, and emphasize the types of existing violence and reporting channels (Unesco, 2014). However, it is still necessary to challenge political, religious, and conservative views that aim to silence these discussions, sustaining misguided narratives that undermine this work, which is essential for holistic development and the construction of a fairer and more inclusive society.